Correction: A secreted proteomic footprint for stem cell pluripotency. - Philip A Lewis; Edina Silajdžić; Helen Smith; Nicola Bates; Christopher A Smith; Fabrizio E Mancini; David Knight; Chris Denning; Daniel R Brison; Susan J Kimber (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0299365.].